Endometrial tissue and blood plasma concentration of ceftiofur and metabolites following intramuscular administration of ceftiofur crystalline free acid to mares. (6th December 2013) - Scofield, D.; Black, J.; Wittenburg, L.; Gustafson, D.; Ferris, R.; Hatzel, J.; Traub‐Dargatz, J.; McCue, P.
Summary Reasons for performing study Systemic administration of ceftiofur crystalline free acid (CCFA) may be a potential treatment for infectious endometritis caused by Streptococcus equi ssp. zooepidemicus (S. zooepidemicus) and other susceptible bacterial organisms in the mare. Objective To determine if i.m. administration of CCFA at the label dose will exceed the minimum inhibitory concentration (MIC) of S. zooepidemicus in the endometrium following single administration and multiple administration protocols. Study design Experimental pharmacokinetic study. Methods Three mares (Group 1) were administered a single i.m. dose of CCFA (6.6 mg/kg bwt) and blood and endometrial biopsies were collected at selected intervals for 144 h. Six additional mares (Groups 2 and 3) received CCFA at times 0, 4, 11 and 18 days, and were sampled at predetermined times for 25 or 49 days, respectively. Plasma and tissue samples were analysed by high‐pressure liquid chromatography with tandem mass spectrometry for desfuroylceftiofur acetamide concentration, which is a direct measure of all ceftofur and ceftiofur metabolites in the sample. Results A mean plasma desfuroylceftiofur acetamide concentration of 0.367 ± 0.0162 μg/ml (mean ± s.e.) was detected at 96 h following administration. Mean endometrial tissue concentration was 0.510 ± 0.0418 μg/g at 96 h and exceeded the MIC for S. zooepidemicus (0.25 μg/ml) throughout the 144 h monitoring period for Group 1. Mares in Groups 2 and 3, given multiple doses of CCFA, maintained plasma concentrations above the MIC for S. zooepidemicus for 25 days. Endometrial tissue levels remained above the MIC at most data collection points for 25 days. Conclusions Ceftiofur crystalline free acid reaches appropriate endometrial tissue values to exceed the MIC of S. zooepidemicus, a common cause of bacterial endometritis. Therefore, CCFA should be effective in the treatment of equine bacterial endometritis caused by S. zooepidemicus and other susceptible bacterial pathogens in the mare.